AN EVALUATION OF MOBILE BANKING USER INTERFACE AND USER EXPERIENCE USING THE FUZZY KANO METHOD: EVIDENCE FROM BCA MOBILE AND PERMATA ME USERS - Palma Juanta; Glenaldo Glenaldo; Raja Zulkarnain Hasibuan (Program Studi Teknik Informatika Universitas Khairun, 2026)
This study aims to evaluate general mobile banking user interface (UI) and user experience (UX) quality using BCA Mobile and Permata ME as representative applications of digital banking services in Indonesia through the Fuzzy Kano approach, which is capable of accommodating uncertainty and subjectivity in user assessments. This study involved 95 active users in Medan City. A total of 20 application features were evaluated based on levels of satisfaction (delight) and dissatisfaction (disgust) and then classified into Must-be, One-dimensional, and Attractive quality attributes. The analysis was conducted in an aggregate manner to capture overall user expectations toward mobile banking applications rather than to compare competitive superiority between the two platforms. The results indicate that the feature “Clear Icons” has the highest priority in the Must-be category, “Well-Organized Transaction History” is the most dominant feature in the One-dimensional category, and “Two-Step Verification for Large Transactions” ranks highest in the Attractive category. These findings suggest that most mobile banking user satisfaction is driven by features with a linear relationship between performance and satisfaction, while additional security features function as satisfaction enhancers. From an academic perspective, this study strengthens the application of the Fuzzy Kano method in evaluating mobile banking UI/UX by emphasizing aggregated user perceptions across multiple applications. Practically, the findings provide guidance for prioritizing feature development to enhance customer satisfaction and loyalty in mobile banking services.